(untitled) (World Science, 2020)
The reproductive system is exposed to various adverse factors and harmful effects at all stages of functioning of an organism. Against the background of declining levels of women’s reproductive health in recent years, there has been a clear tendency towards an increase in the number of patients with pathology of puberty. The low level of somatic and reproductive health before pregnancy causes a high incidence of complicated labors, which leads to a deterioration in the development of subsequent generations. The purpose of the study. To provide clinical characteristics of women who had menstrual dysfunction in puberty, which were based on the study of clinical and anamnestic data, laboratory and instrumental research methods, analysis of risk factors, clinical course, treatment effectiveness and dispensary observation. Materials and methods. According to the nature of the disfunctions, the main group of women (n = 210) who had menstrual disorders in puberty was divided into 3 subgroups (n = 70): the first - women with primary oligomenorrhea and timely average menarche, the second - with late menarche, the third - with pubertal bleeding. The control group included women (n = 70) with the correct rhythm of menstruation in puberty. Results. The clinical prospective study analyzed the social status of women with reproductive dysfunction in puberty, the frequency and structure of existing concomitant somatic diseases, the duration of the menstrual cycle, the nature of diseases of the female genital organs; the assessment of the comprehensive treatment of revealed disorders, which allowed to obtain a favorable reproductive prognosis. The majority of surveyed women (53.3%) planned a pregnancy, which occurred in 75.9% from among of planning ones. Conclusions. The conduction of clinical and anamnestic analysis of the reproductive function of women with menstrual dysfunction in puberty will increase the effectiveness of the treatment of identified disorders and will allow developing algorithms for management of such women during planning and during pregnancy.